Entrepreneurship, Institutions and Skills in Low-Income Countries - Zuzana Brixiova; Balázs Égert (Institute of Labor Economics (IZA), 2017)
This paper develops a model of costly firm creation in an economy with weak institutions, costly business environment as well as skill gaps where one of the equilibrium outcomes is a low-productivity trap. The paper tests the implications of the model using a cross-sectional dataset including about 100 countries. Both theoretical and empirical results suggest that to move the economy into a productive equilibrium, complementarity matters: reforms to improve the business environment tend to be more effective in creating productive firms when accompanied by narrowing skill gaps. Similarly, more conducive business regulations amplify the positive impact on firm creation of better education and reduced skill mismatches. To escape a low-productivity trap, policymakers should thus create a pro-business framework and a well-functioning education system.
Keywords: L26; J24; J48; O17; 330; model of start-ups and strategic complements; institutions; education; low-income countries; threshold regression